Synthesis and crystallization behavior of regioregular-block-regiorandom poly(3-hexylthiophene) copolymers. Issue 23 (29th November 2018) - Kim, Jin-Seong; Choi, Jee-Eun; Park, Hyeonjung; Kim, Youngkwon; Kim, Hyeong Jun; Han, Junghun; Shin, Jae Man; Kim, Bumjoon J.
Abstract : Regioregular–regiorandom poly(3-hexylthiophene) copolymers, synthesized by chain-transfer polycondensation, show strong crystallinity due to their one-sided distribution of regiodefects. Abstract : Herein, we report the development of poly(3-hexylthiophene) regioblock copolymers ( block -P3HTs), which are composed entirely of identical 3-hexylthiophene repeating units, with one block being highly regioregular ( rre ) and the second block being regiorandom ( rra ). This block -P3HT was prepared via catalyst-transfer polycondensation by the sequential addition of different monomer batches, with 3-hexylthiophene (3HT) monomers used for the rre block and a mixture of 3HT and 3, 3′-dihexyl-2, 2′-bithiophene (BT) monomers for the rra block. The average regioregularity (RR avg ) of the block -P3HTs was tuned from 58 to 79% by differentiating the weight ratio between the rre and rra blocks, and the crystalline behavior of block -P3HTs in comparison with polymers having similar RR avg but a random distribution of 3HT and BT units ( co -P3HT) was investigated. This study allowed for the exploration of the effects of the distribution of regiodefects within the polymer chain ( e.g. confined to a single block versus uniformly distributed throughout the polymer) on the crystalline behaviors of the polymer. For example, block -P3HT with 72% RR avg formed long nanowires by solution assembly, due to the strong crystallinity from a sufficient effective conjugation length in the rre block, whereas co -P3HT with the same RR avg formed spherical micelles indicating amorphous characteristics. Overall, the block -P3HTs showed a strong tendency to crystallize, even with very low RR avg, driven by the rre block in the polymers, whereas the crystallinity of the co -P3HTs was substantially suppressed due to chain distortion by the distributed regiodefects.